Sustainability benefits of RFID technology in Vietnamese fashion supply chain - Rajkishore Nayak; Majo George; Irfan Ul Haq; Hiep Cong Pham (Cleaner Logistics and Supply Chain)
The growing need for sustainability in fashion production and retail operations has prompted the adoption of a variety of strategies, including the use of technology. Radio Frequency Identification (RFID) technology may shift economic dynamics and provide a more sustainable future in numerous industries, including fashion. Vietnam is one of the main fashion and textile manufacturing nations in South East Asia, where the manufacturing sectors face a number of obstacles in order to reach the triple bottom line of sustainability. As a result, using empirical research, this paper aimed to analyse the long-term advantages of RFID technology implementation. The research findings revealed that the adoption of RFID technology in Vietnamese fashion enterprises is in its infancy stage. Among a number of factors, cost of deploying RFID technology is found to be a critical barrier. Furthermore, companies that have used RFID have demonstrated that the speed, precision, and on-time information availability provided by RFID assists in reaching a variety of environmental, social, and economic advantages. Although this study discovered certain disadvantages of deploying RFID technology, the benefits obtained by RFID technology outweigh the disadvantages. The findings suggest that fashion industry should migrate to RFID due to the benefits of sustainability and transparency in the supply chain.